Magnetic Agarose Microspheres/Hyaluronic Acid Hydrogel as a Trackable Bulking Agent for Vesicoureteral Reflux Treatment - Chen, Hong; Wu, Pan; Xu, Hong; Wang, Changchun (Frontiers in Bioengineering and Biotechnology, 2021)
Vesicoureteral reflux (VUR) is one of the most common congenital anomalies in kidney and urinary tract. Endoscopic subureteral injection of a bulking agent has become popular in VUR treatment due to its high success rates, few complications and straightforward procedure. In this study, a novel magnetic bulking agent was prepared by embedding Fe3O4 magnetic nanoparticles in cross-linked agarose microspheres with diameters of 80-250 um and dispersing the magnetic microspheres in hyaluronic acid hydrogel. The bulking agent has good biocompatibility and biosecurity validated by the tests of cytotoxicity, in vitro genotoxicity, animal irritation, skin sensitization, acute systemic toxicity, and pathological analysis after injection of the bulking agent extract solution into healthy mice as well as injection of the bulking agent into VUR rabbits. The VUR rabbits were created by incising the roof of the intravesical ureter to enlarge the ureteral orifice. The success rate of the bulking agent in treating VUR rabbits using subureteral transurethral injection technique was 67% (4/6) or 80% (4/5, excluding the unfinished rabbit), and no migrated particles were found in the organs of the rabbits. The transverse relaxation rate of the bulking agent was 104/mM s. After injection, the bulking agent was long-term trackable through magnetic resonance imaging that can help the clinicians to inspect the VUR treatment effect. For the first time, this study demonstrates that the bulking agent with long-term stable tracer is promising for endoscopic VUR treatment.